Espaço-corpo-grafias: experiências para uma pedagogia do corpo na arquitetura - Eichemberg, Maria Júlia Barbieri (2022)
For a long time, the body-space relationship, as far as architecture is concerned, was determined by the idea of a body understood only in its objective nature: a unit of measurement that related to space in a dimensional way. This reverberated in different ways on the spaces produced, since architecture has understood the body in its ideal nature and not in its subjective nature. The objective of this thesis is to seek possibilities to establish other pedagogical practices for Architecture, through which the processes and spaces do not neglect the body, but seek, from it, other modes of existence for learning. To do so, we start from the Bodymedia Theory (KATZ & GREINER, 2007) and from the contributions of Cognitive Science studies, especially the notion of Embodied Mind and the Enactive Theory of Perception (VARELA, 2003). We propose a Pedagogy of the Body for teaching processes in Architecture that is structured around four fundamental environments: objects, the house, the place and the city. The methodology is based on action research and cartography practice brought here by several authors such as DELEUZE & GUATTARI (1995), KASTRUP (2007) and ROLNIK (2011), which allow us to present this process from its rhizomatic nature, both in the pedagogical strategies proposed in the teaching environment and in this research. The idea is to create a landscape available to those who access this cartography. For that, the elements that build the maps were conceived during ffteen years of teaching, and the teaching experience is at all times managing the students’ learning experience. This means that at the same time that a world is invented for the teaching experience to happen, it is also invented by it